2021
DOI: 10.3389/fendo.2021.702558
|View full text |Cite
|
Sign up to set email alerts
|

Progestin-Primed Ovarian Stimulation Protocol for Patients in Assisted Reproductive Technology: A Meta-Analysis of Randomized Controlled Trials

Abstract: ObjectivesProgestin-primed ovarian stimulation (PPOS) is a new ovarian stimulation protocol that can block the luteinizing hormone (LH) surge through progesterone instead of traditional down regulating or gonadotropin-releasing hormone (GnRH) antagonist, and in order to achieve multi-follicle recruitment. This paper aims to investigate the effectiveness of PPOS and its suitability for infertile patients with different ovarian reserve functions.MethodsWe searched published randomized controlled trials (RCTs) ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…This is in contrast to the findings of a randomized controlled trial (RCT) in women with PCOS comparing PPOS with dydrogesterone 20 mg beginning on CD2 to Cetrotide starting with follicle size of 12-13 mm [27 ]. Eftekhar et al [28] similarly report suppressed LH levels on the day of trigger in both the PPOS and antagonist groups, however the LH level was significantly higher in the PPOS group. They also found lower implantation (7.32% vs. 15.69%) and clinical pregnancy rates (14.6% vs. 29.4%) among the PPOS group compared to the GnRH antagonist group in the subsequent frozen embryo transfer cycles, though these were not statistically significant.…”
Section: Methods and Timing Of Ovulation Suppressionmentioning
confidence: 90%
“…This is in contrast to the findings of a randomized controlled trial (RCT) in women with PCOS comparing PPOS with dydrogesterone 20 mg beginning on CD2 to Cetrotide starting with follicle size of 12-13 mm [27 ]. Eftekhar et al [28] similarly report suppressed LH levels on the day of trigger in both the PPOS and antagonist groups, however the LH level was significantly higher in the PPOS group. They also found lower implantation (7.32% vs. 15.69%) and clinical pregnancy rates (14.6% vs. 29.4%) among the PPOS group compared to the GnRH antagonist group in the subsequent frozen embryo transfer cycles, though these were not statistically significant.…”
Section: Methods and Timing Of Ovulation Suppressionmentioning
confidence: 90%
“…Moreover, advanced vitrification techniques and the freeze-all embryo strategy made the protocol widely used. In some prospective and retrospective cohort studies, comparable embryological and clinical outcomes were observed between the PPOS protocol and the conventional ovarian stimulation protocol, which implied that the embryo development potential could not be impaired ( 35 , 36 ). A previous study has demonstrated no significantly elevated rate of congenital anomalies for infants after the treatment with LPS compared with the conventional ovarian stimulation protocol ( 37 ).…”
Section: Discussionmentioning
confidence: 96%
“…P4 secreted by the corpus luteum strongly inhibited pulsatile GnRH and LH secretion ( 21 ). Progestin-primed ovarian stimulation (PPOS) is an ovarian stimulation protocol that can block the LH surge through oral progesterone instead of the traditional down-regulating or GnRH antagonist ( 22 ). In patient 1 without glucocorticoid pretreatment, we presumed that endogenous LH secretions could be suppressed in a PORD female patient with elevated P4, which is the “natural PPOS” protocol.…”
Section: Discussionmentioning
confidence: 99%